Heart Genomics (Translational Bioinformatics, 2018)
This book elucidates how advances in genomics research are being applied in connection with heart diseases. It describes the development of genome-scale technologies and their applications to all areas of cardiac investigations, such as genomics, functional genomics, epigenomics, etc., and how they relate to a series of important breakthroughs in various heart diseases. Applying unbiased genomics, combined with a disease-focused and hypothesis-driven approach, represents a promising way to advance our understanding of cardiac diseases. The book offers an important reference work on introducing genomics in heart disease for all scientists and graduate students whose work involves genomics and cardiology, as well as for clinical physicians.